Tuberculous meningitis - Thwaites, G (2013)
Tuberculous meningitis (TBM) is caused by Mycobacterium tuberculosis and kills or disables around a half of sufferers. It is commonest in young children and those infected with HIV, but can affect all age-groups. TBM presents with non-specific symptoms over days or weeks, followed by worsening headaches, fever, and vomiting. Without anti-tuberculosis chemotherapy, cranial nerve palsies (typically VIth and IIIrd nerves) and hemiplegia may develop, and consciousness becomes impaired. Mortality exceeds 50% if the Glasgow Coma Scale score is less than 10/15 by the time the patient starts treatment. Early diagnosis and treatment improves outcome but is notoriously difficult as current laboratory tests lack sensitivity. Early empirical therapy is often required to improve the chance of survival. Rifampicin-based anti-tuberculosis chemotherapy should be used whenever possible and given for 9-12 months. Adjunctive corticosteroids are recommended for all patients with TBM for the first 6-8 weeks of treatment, regardless of age, disease severity, or HIV infection. Hydrocephalus, cerebral infarction, and expanding tuberculoma are common complications of TBM, occurring at any time before or after treatment starts. Brain imaging, preferably with MRI, is recommended to assess the evolution and management of these complications. Ventriculo-peritoneal shunting should be considered in those with hydrocephalus and falling consciousness. © 2013 Elsevier Ltd. All rights reserved.